(untitled) (Research, Society and Development, 2022)
This work aimed to contribute to the evaluation of a solar drying system used in the drying of kaolin, developed to be applied in the region of the Pegmatitic Province of Borborema (PPB). The drying process was analyzed for the climatic conditions of the city of Campina Grande in the state of Paraíba, comparing the advantages and disadvantages of using three types of coverage in the solar drying system: polycarbonate, polypropylene and without coverage. As a methodology, three experiments were carried out, two in identical solar dryers, with direct exposure, one with a polycarbonate cover and another with a polypropylene cover, the third experiment was with solar drying in the open air. The experiments were performed on the same day and at the same location to allow comparisons. The drying time of the kaolin, the thermal efficiency of each drying system, the amount of water removed from the kaolin per unit of time and the specific energy consumption for each experiment were evaluated. The kaolin used had an initial moisture content, on a wet basis, of 30%, and each kaolin sample had 1000 g. The main experimental results obtained showed that the solar drying reduced the kaolin moisture from 30% to 5%, leaving it in suitable conditions for the following stages of processing. In conclusion, it was observed that the solar dryer with polycarbonate cover was more thermally efficient (38.24%) compared to the dryer with polypropylene cover (35.59%), in addition to the dry kaolin reaching the water content in desired wet base in less time. The dryer with a polycarbonate cover also obtained lower specific energy consumption rates, thus requiring less energy to carry out the drying process.